Investigation on the Properties of 3D Warp Interlock Fabrics Based on Moroccan Sisal Yarns as Reinforcement for Composite Materials. Issue 13 (1st December 2022) - Samouh, Zineb; Abed, Ahmed; Cherkaoui, Omar; Soulat, Damien; Labanieh, Ahmad Rashed; Boussu, François; Elmoznine, Reddad
ABSTRACT: Despite the variability of Moroccan natural resources, few Moroccan natural fibers are exploited as natural textile composites. This study aims to investigate the characteristics of 3D warp interlock fabrics based on Moroccan sisal yarns. Before weaving, the characteristics of sisal yarns have been analyzed following standards. Based on these natural yarns, six different 3D fabric architectures were manufacturing on the same manual dobby loom. During the weaving process, process parameters have been kept constant for all the 3D woven architectures to ensure a similar value for both the warp and weft yarn densities. Different values of the fabric areal density and thickness of 3D fabrics have been measured under the same test and related conditions. Different parameters play an important role on these different product parameter values as; the non-regularity of the yarn and the significant differences of warp and weft shrinkages depending on the 3D woven architecture. At the same time, yarn damage has been checked before and after the weaving of the produced 3D woven preforms. At the end of this study, new knowledge on the mechanical performance of 3D warp interlock sisal fabric have been revealed for facilitating the suited choice of architecture for a composite material solution.